Mori Cortex radicis extract protected against diet-induced neuronal damage by suppressing the AGE-RAGE/MAPK signaling pathway in C. elegans and mouse model. (April 2022) - You, SoHyeon; Jang, Miran; Kim, Gun-Hee
Graphical abstract: Highlights: MCR suppressed lipid and AGEs accumulation and ROS, and improved cognitive functions in glucose-fed C. elegans. MCR attenuated metabolic disorder and spatial memory in high fat/liquid sugar diet-fed mouse. Diet-induced MetS mouse model increased AGEs deposit, pro-inflammatory cytokines and AD-related factors. These MetS derived neuronal damages was inhibited by MCR intake via AGE-RAGE/MAPK pathway. Abstract: In this study, the underlying mechanisms of metabolic syndrome (MetS) and the risk of AD factors, and the effect of dietary Mori cortex radicis (MCR) were investigated in two in vivo models. In glucose-induced C. elegans, MCR attenuated metabolic disorder by inhibiting lipid and advanced glycation end products (AGEs) production, reducing oxidative stress, and preventing cognition and behavioral deficits. In high fat/liquid sugar-induced MetS mice, MCR intervention improved metabolic alterations and spatial memory. Furthermore, MCR in diet suppressed AGEs deposit and RAGE expression, improved the antioxidant system, and decreased pro-inflammatory cytokine levels in mouse hippocampus. This was accompanied by downregulation of the MAPK (p38, ERK, and JNK) pathway, which consequently protected against brain damage by suppressing BACE-1, APP, Tau, and Aβ. These findings may be valuable for those investigating crosstalk between MetS and neurodegenerative disease progression or the effect of MCR on the AGE-RAGE/MAPK pathway.